Short path molecular distillation of the essential oil from Pinus roxburghii oleoresin affords volatile fractions with powerful antioxidant and antimicrobial activities comparable with common synthetic agents and antimicrobials - Muhammad Adnan Ayub; Hawraz Ibrahim M. Amin; Rameen Waseem; Kamaran Younis M. Amin; Muhammad Asif Hanif; Amjad Hussain; Kovan Dilawar Issa; Jorge Ramírez; Chabaco Armijos; Muhammad Zubair; Giovanni Vidari (Heliyon)
The primary purposes of this work were to study the influence of the distillation temperature on the yield of the turpentine essential oil hydrodistilled from the Pinus roxburghii oleoresin and to obtain products with powerful bioactivities by short path molecular distillation of the oil. Our findings showed that the hydrodistillation temperature affected the yield as well as the antioxidant and antimicrobial properties of the essential oil: the highest yield (20.27 %) and bioactivities were obtained for the oil distilled at 180 °C. The oil was subsequently separated by short path molecular distillation into fractions and sub-fractions whose antioxidant activity was determined by the DPPH scavenging assay, the inhibition of linoleic acid peroxidation test, the FRAP assay, and the H2O2 scavenging assays. In addition, the antimicrobial activity of the fractions and sub-fractions against the bacteria Pasteurella multocida, Staphylococcus aureus, Escherichia coli, and Bacillus subtilis, and the fungal strains Fusarium solani, Alternaria alternata, Aspergillus flavus, and Aspergillus niger, was measured by the agar well diffusion method, the microdilution broth assay and the resazurin microtiter plate test. The antioxidant and antimicrobial activities varied between fractions and subfractions; however, their overall potency makes the P. roxburghii oleoresin a potential source of valuable natural antimicrobial products employable against various foodborne microbes and molds, as well as a source of preservative agents against food oxidation. Longifolene, 3-carene, α-pinene and β-pinene were identified by GC-MS analysis as the main constituents of the P. roxburghii turpentine essential oil and the most active fractions and sub-fractions. These terpenes were likely responsible for the bioactivity of the volatile mixtures.